Antecedents and Consequences of Status Consumption Among Urban Vietnamese Consumers - Mai, Nguyen Thi Tuyet; Tambyah, Siok Kuan (Organizations and Markets in Emerging Economies, 2011)
This study examines the antecedents and consequences of status consumption in the transitional economy of Vietnam. Both qualitative (focus groups and in-depth interviews) and quantitative methods (survey) were employed in this investigation. To test the proposed model and hypotheses, a large consumer survey was conducted in the two biggest cities in Vietnam. The results of Structural Equation Modeling provided empirical evidence for the significant impact of most of the proposed antecedents of status consumption. Specifically, modern status orientation, the ‘success’ component of materialism, and both the individualistic self and collectivistic self were found to have a positive impact on status consumption. Traditional status orientation and consumer ethnocentrism were found to be negatively related to status consumption. The findings also suggested the positive consequences of status consumption on satisfaction with status consumption and satisfaction with life in general. Discussion of the research findings and managerial implications are also provided.
Keywords: status consumption; status orientation; materialism; transitional economy; Vietnam